2013
DOI: 10.1016/j.jvs.2012.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in carotid plaque features and inflammation

Abstract: Carotid plaques seem significantly different in women and men, but the main drivers of such pathologic differences are baseline features, including stenosis severity and symptom status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
41
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 40 publications
9
41
0
4
Order By: Relevance
“…In our study, only smoking was more prevalent among men, which is in agreement with other studies that also found a greater frequency of smoking among men with peripheral and atherosclerotic carotid diseases [6][7][8] . As our study was retrospective, only current smoking was analyzed.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In our study, only smoking was more prevalent among men, which is in agreement with other studies that also found a greater frequency of smoking among men with peripheral and atherosclerotic carotid diseases [6][7][8] . As our study was retrospective, only current smoking was analyzed.…”
supporting
confidence: 93%
“…Those authors included patients with claudication in their sample and found a significantly higher percentage of critical ischemia among women that underwent treatment than among men 6 . The higher prevalence of hypertension among women was also found by other authors in studies about CVD 8,9,11 . Su et al found an increase in the prevalence of hypertension among women after menopause 9 .…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Sangiorgi et al [27] found that thrombotic plaques were significantly more common in men than in women. They also found that plaque ulceration was found more often in men, whereas women had a higher degree of calcific nodules and stable fibrocalcific plaque.…”
Section: Gender and Atherosclerosis: Difference In Plaque Morphologymentioning
confidence: 99%
“…In addition, 33.0% of US adults, or approximately 78 million people over 20 years of age, have hypertension. Unfortunately, this is a major public health problem because although nearly 82% of people with hypertension are aware of their condition, a smaller fraction (75%) are using antihypertensive medication; but more important, only 53% of those with hypertension are controlled to target Reducing stroke in women with risk factor management: blood pressure and cholesterol future science group Review Baghshomali & Bushnell levels [1].…”
mentioning
confidence: 99%